Reloading mechanical characteristics of cemented tailings backfill after dynamic loading action - Xuepeng SONG; Bowen FAN; Shi WANG; Hongwei ZHANG (Meitan xuebao)
Blasting excavation and cavity filling are the core means of filling mining in underground metal mine. As the core load-bearing unit of cavity, the backfill is inevitably subjected to the blasting dynamic load perturbation of adjacent ore body, which in turn induces some structural changes in the internal structure of matrix and affects its re-bearing capacity and stability, which is related to the safety of mine production. Therefore, in this paper, the dynamic damage filling body considering the magnitude of impact amplitude is prepared based on the split Hopkinson press bar system (SHPB), and the simulation of filling body blasting disturbance is realized. The mesoscopic structural response characteristics of the filling body under dynamic loading are investigated, the mechanical behavior and crack extension mechanism of the dynamically damaged filling body are revealed, and the instability over-warning of the dynamically damaged filling body is realized. The results show that: the degradation of meso-structure of the dynamically damaged filling body increases with the increase of impact amplitude, corresponding to the increase of porosity by 34.48%, the decrease of wave velocity by 44.48%, and the intensification of the initial damage degree. With the increased impact amplitude, the uniaxial compressive strength and elastic modulus of the dynamically damaged filling body show a three-stage trend of slow decrease, then rapid decrease and then slow decrease, with the maximum decrease rate of 54.15% and 69.02%, respectively. Meanwhile, the compaction stage of the stress-strain curve of the dynamically damaged filling body is significantly prolonged with the increase of the damage degree. The peak strain increases by 78.35%, and the filling body changes from brittle ductile to ductile. The characteristic parameters of acoustic emission (AE) are closely related to the rupture behavior of the filling body. Due to the difference in the initial damage degree, the rate, number and scale of cracks sprouting, expanding and propagating within the matrix of the dynamically damaged filling body are significantly different. The activity and sparsity of the AE signal initially decrease, then increase, and finally decrease again with the increase in impact amplitude. The AE ib value exhibits a pattern of “fluctuating increase”, “sharp decrease”, and “large fluctuation”. As the impact amplitude increases, there is an increase in the area of sharp decline in AE ib values and a shift to the pre-peak stage. The area of sharp decline in ib value is judged to be the precursor information of instability, and the dynamic damage filling body reaches the critical value of instability at a smaller stress. Increasing the impact amplitude has no significant effect on the failure mode of the dynamically damaged filling body, but the area of the surface collapse zone is increased and the degree of failure is significantly enhanced.